A versatile efficient one-step approach for carbazole–pyridine hybrid molecules: highly efficient host materials for blue phosphorescent OLEDs. Issue 9 (15th December 2014) - Tang, Chao; Bi, Ran; Tao, Youtian; Wang, Fangfang; Cao, Xudong; Wang, Shifan; Jiang, Tao; Zhong, Cheng; Zhang, Hongmei; Huang, Wei
Abstract : A series of carbazole–pyridine hybrid hosts were prepared by a convenient catalyst free C–N coupling reaction for high-efficiency blue electrophosphorescence. Abstract : By using various fluoro-substituted pyridines and carbazole as starting materials, we have synthesized a series of carbazole–pyridine hybrid compounds through an efficient catalyst free C–N coupling reaction with high yields of 85–95%. The bi-, tri- and tetra-carbazole substituted pyridine derivatives exhibit increased thermal stabilities and comparatively high triplet energy levels of ∼3.0 eV. By using them as host materials for blue phosphorescent OLEDs, maximum current efficiencies are achieved ranging from 32–42 cd A −1 .